2023
DOI: 10.1002/jssc.202200770
|View full text |Cite
|
Sign up to set email alerts
|

Development, stability‐indicating assessment, and evaluation of influential method conditions using a full factorial design for the determination of Nintedanib esylate‐related impurities

Abstract: The design of an appropriate analytical method for assessing the quality of pharmaceuticals requires a deep understanding of science, and risk evaluation approaches are appreciated. The current study discusses how a related substance method was developed for Nintedanib esylate. The best possible separation between the critical peak pairs was achieved using an X-Select charged surface hybrid Phenyl Hexyl (150 × 4.6) mm, 3.5 μm column. A mixture of water, acetonitrile, and methanol in mobile phase-A (70:20:10) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Both methods were developed and validated considering the International Council for Harmonization (ICH) requirements, which met its acceptance criteria and were found to be specific, linear, accurate, precise, and robust [24][25][26][27][28]. The results of the forced degradation study confirmed that the developed RP-HPLC-UV method is stabilityindicating, in addition to being specific and selective in the separation and quantitative determination of organicrelated impurities of chlorzoxazone drug substance and drug product [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Both methods were developed and validated considering the International Council for Harmonization (ICH) requirements, which met its acceptance criteria and were found to be specific, linear, accurate, precise, and robust [24][25][26][27][28]. The results of the forced degradation study confirmed that the developed RP-HPLC-UV method is stabilityindicating, in addition to being specific and selective in the separation and quantitative determination of organicrelated impurities of chlorzoxazone drug substance and drug product [29,30].…”
Section: Introductionmentioning
confidence: 99%